Occupational adjustment of immigrants - Aslan Zorlu (Institute for the Study of Labor (IZA), 2011)
This paper examines the speed of the occupational adjustment of immigrants using Labour Force Surveys 2004 and 2005 from Statistics Netherlands. The analysis provides new evidence that immigrants start with jobs at the lower levels of skill distribution. Their occupational achievement improves significantly with the duration of residence. The extent of this initial disadvantage and the rate of adjustment vary across immigrant groups according to the transferability of skills associated with their cultural and linguistic distance from Dutch society as predicted by the theory of immigrant occupational mobility. Most notably, Turks and Moroccans face the greatest initial dip and achieve the highest rate of adjustment while the opposite holds for Caribbean and Western immigrants. Our results are robust to three alternative measures of occupational status.
urn:nbn:de:101:1-2012010913672
Keywords: J15; J24; 330; ethnic minorities; quality of jobs; Migranten; Ethnische Gruppe; Unterbeschäftigung; Anpassung; Berufliche Integration; Schätzung; Niederlande